Michela Spataro & Alexandra Villing (eds.), Ceramics, Cuisine and Culture: The Archaeology and Science of Kitchen Pottery in the Ancient Mediterranean World - Rosenthal-Heginbottom, Renate (Journal of Hellenistic Pottery and Material Culture, 2017)
The excellent volume under review, presenting twenty-three papers and covering diverse periods, geographical regions, cultural and ethnic identities, is the fruit of the conference »Ceramics, cuisine and culture: the archaeology and science of kitchen pottery in the ancient Mediterranean world«, held at the British Museum in December 2010. It is a masterly interdisciplinary research volume with the participation of forty scholars, and the editors deserve our honest admiration and gratitude. After a comprehensive introduction by the editors (Chapter 1 – Investigating ceramics, cuisine and culture – past, present and future), referred to in John Tidmarsh’s review, the papers are grouped under three main headings – How to make a perfect cooking pot: technical choices between tradition and innovation (Part I); Lifting the lid on ancient cuisine: understanding cooking as socio-economic practice (Part II); New pots, new recipes? Changing tastes, culinary identities and cross-cultural encounters (Part III). The last paper is a postscript by Y. Kyriakopoulos on Aegean cooking pots in the modern era (1700–1950), followed by an index. Each paper is provided with an extensive bibliography.